Montane regions shape patterns of diversification in small mammals and reptiles from Madagascar's moist evergreen forest. (5th September 2020) - Everson, Kathryn M.; Jansa, Sharon A.; Goodman, Steven M.; Olson, Link E.
Abstract: Aim: Madagascar is renowned for its exceptional species diversity and endemism. The island's mountainous regions are thought to have played a role in lineage and species diversification, but this has yet to be explored across taxonomic groups and a temporal context has not yet been identified. We tested whether montane regions have promoted population divergence in Madagascar's vertebrate fauna and, if so, whether these divergence events were contemporaneous. Location: Moist evergreen forests of Madagascar. Taxa: Small mammals and reptiles. Methods: We analysed mitochondrial DNA data from 20 small‐mammal and five reptile species widely distributed across Madagascar's moist evergreen forests. We used phylogenetic and population genetic analyses to identify major phylogeographic patterns, then used linear regression to determine if the strength of phylogeographic structure is related to taxon, body size or elevation. Finally, we tested whether or not divergence across highlands occurred synchronously in multiple species, and used simulations to assess the power of these analyses to accurately estimate divergence times. Results: We observed a shared phylogeographic pattern across multiple species that suggests Madagascar's northern, central and southern highlands have served as important regions of diversification on Madagascar. This pattern was recovered across taxa with varying body sizes and elevational distributions. We also identified four pulses of divergence between the northern and central highlands since the late Miocene, although simulations suggest that our empirical data cannot recover the number or timing of divergence events with high certainty. Finally, we observed several instances of deep intraspecific genetic splits, suggesting that several of the species we evaluated may represent cryptic species complexes. Main Conclusions: We identified a highland‐driven phylogeographic pattern plus several cases of cryptic endemism and recent speciation, which have important evolutionary and conservation implications. This work presents a new phylogeographic hypothesis for recent diversification on Madagascar, reaffirms the urgent need for continued collection of voucher specimens and illuminates areas of particular importance for safeguarding genetic diversity in one of the world's foremost and threatened biodiversity hotspots.